Job Seekers' Perspectives on the Use of AI Chatbots in the Recruitment Process - Monica, M; Bhasha , Vali; Ramanaiah , G; Kumar , Sendhil (Electronic Journal of Business and Management, 2023)
Recruitment is a crucial aspect for companies, involving a significant investment of time and resources. To streamline the process, many organizations are turning to AI chatbots that emulate human intelligence. This study evaluates the effectiveness of AI chatbots in recruitment from the perspective of job seekers. Using an exploratory research design, we surveyed 100 respondents actively seeking employment, selected through the snowball sampling technique. We analyzed the collected data using statistical techniques, focusing on identifying tasks suitable for AI chatbots in recruitment. The study also aims to pinpoint areas for improvement to better meet the needs of job seekers. The results indicate that job seekers have a moderate level of familiarity and comfort with AI chatbots during the recruitment process. Their opinion on the overall accuracy and effectiveness of chatbots in addressing queries is neutral. Job seekers, however, perceive AI chatbots as moderately effective in providing relevant information about the job application process and matching skills and qualifications with job openings. They also find chatbots reasonably effective in scheduling interviews, conducting assessments, and facilitating post-interview communication. While job seekers acknowledge the moderate effectiveness of AI chatbots in specific tasks, they maintain a neutral stance on their reliability for all aspects of the recruitment process. These findings provide valuable insights for organizations aiming to enhance the integration of AI chatbots in their recruitment processes and improve the overall job-seeking experience.